2016
DOI: 10.5539/jel.v6n1p27
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Variables Predicting Faculty of Education Students’ Speaking Anxiety through Ordinal Logistic Regression Analysis

Abstract: The purpose of this study is to determine whether Cumhuriyet University Faculty of Education students' levels of speaking anxiety are predicted by the variables of gender, department, grade, such sub-dimensions of "Speaking Self-Efficacy Scale for Pre-Service Teachers" as "public speaking", "effective speaking", "applying the speaking rules", "organizing the speech content", and "evaluating the speech". Correlational survey model is employed in the study. While the dependent variable of the study is students' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
4
0
6
Order By: Relevance
“…In addition, the most used method was the survey model. Lüle Mert, 2015;İşçan and Karagöz, 2016;Baki and Kahveci, 2017;Bozpolat, 2017;Arslan, 2018;Deringöl, 2018;Gölpınar, vd., 2018;.This result may have been due to the researchers' desire to generalize the research results through the survey model and the opportunity to collect data more easily from large sample groups. Experimental designs were also used in some of the studies (Katrancı and Aydoğan, 2016;Bulut, Açık and Çiftçi, 2016;Tüzemen, 2016;Asan, 2019;Demirci, 2019).No research was found in which only the qualitative method was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the most used method was the survey model. Lüle Mert, 2015;İşçan and Karagöz, 2016;Baki and Kahveci, 2017;Bozpolat, 2017;Arslan, 2018;Deringöl, 2018;Gölpınar, vd., 2018;.This result may have been due to the researchers' desire to generalize the research results through the survey model and the opportunity to collect data more easily from large sample groups. Experimental designs were also used in some of the studies (Katrancı and Aydoğan, 2016;Bulut, Açık and Çiftçi, 2016;Tüzemen, 2016;Asan, 2019;Demirci, 2019).No research was found in which only the qualitative method was used.…”
Section: Resultsmentioning
confidence: 99%
“…Araştırmalarda kullanılan yöntemlere bakıldığında çoğunluğu nicel araştırma yöntemlerine dayalı yürütülmüştür (Tablo 2). Ayrıca en fazla tarama modeli kullanılmıştır (Arslan,2018;Bozpolat, 2017;Baki ve Kahveci, 2017;Deringöl, 2018;Gölpınar vd., 2018;İşçan ve Karagöz, 2016;Kavruk ve Deniz,2015;). Tarama modeli bir konu ya da olaya ilişkin kişilerin görüşlerinin veya ilgi, beceri, yetenek, tutum gibi özelliklerinin saptandığı; geniş bir kitleyi temsil edecek örneklemin seçildiği, verilerin toplanmasında veri kaynağından alınan cevaplara dayanan bir araştırma modelidir (Büyüköztürk ve diğerleri, 2017).…”
Section: Sonuç Temasına Ait Bulgularunclassified
“…This model is implemented as an alternative to a discriminant analysis when the normal model is not applicable. According to Bozpolat [79], the main objective of logistic regression analysis is to establish an acceptable model with a good fit that can identify the relationship between the predicting and predicted variables by using a minimum number of variables.…”
Section: Statistical Modelmentioning
confidence: 99%
“…Literatürdeki araştırmalarda da benzer ve farklı sonuçlarla karşılaşılmaktadır. Hayran (2020) ve Bozpolat (2017) tarafından yapılan araştırmalarda da bölüm değişkeninin, konuşma öz yeterlik algısı üzerinde etkisinin olduğu ortaya çıkarılmıştır. Ancak Baki (2018), Başaran ve Erdem'in ( 2009) yapmış olduğu araştırmalarda, öğretmen adaylarının eğitim gördükleri bölümlerin konuşma öz yeterliği üzerinde bir etkiye sahip olmadığı ortaya çıkarılmıştır.…”
Section: Sonuç Ve Tartışmaunclassified